High Performance Grinding and Advanced Cutting Tools - Jackson, Mark J.; Hitchiner, Michael P.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
High Performance Grinding and Advanced Cutting Tools discusses the fundamentals and advances in high performance grinding processes, and provides a complete overview of newly-developing areas in the field. Topics covered are grinding tool formulation and structure, grinding wheel design and conditioning and applications using high performance grinding wheels. Also included are heat treatment strategies for grinding tools, using grinding tools for high speed applications, laser-based and diamond dressing techniques, high-efficiency deep grinding, VIPER grinding, and new grinding wheels.
Abrasive Tools and Bonding Systems -- Abrasive Grain Characteristics -- Silicon Carbide -- Fused Alumina -- Alumina Zirconia -- Ceramic Sol-gel Alumina Abrasive -- Superabrasives -- Vitrified Bonding Systems and Heat Treatment -- Vitrified Bonding Systems -- Grinding Wheel Structure During Heat Treatment -- Case Study I -- Case Study II -- Conclusions.
Keywords: Engineering; Machinery; Materials; Engineering; Manufacturing, Machines, Tools; Metallic Materials; Machinery and Machine Elements